Resistance to change - James Dow; Enrico Perotti (Fondazione Eni Enrico Mattei (FEEM), 2010)
Established firms often fail to maintain leadership following disruptive market shifts. We argue that such firms are more prone to internal resistance. A radical adjustment of assets affects the distribution of employee rents, creating winners and losers. Losers resist large changes when strong customer goodwill cushions the consequences. Partial adaptation may lead winners to depart to form new firms with no goodwill, but no internal resistance.
Keywords: D21; 330; Resistance to Change; Leadership; Adaptation